Hexagonal two layers-photonics crystal fiber based on surface plasmon resonance with gold coating biosensor easy to fabricate - Dedi Irawan; Khaikal Ramadhan; Saktioto Saktioto; Fitmawati Fitmawati; Dwi Hanto; Bambang Widiyatmoko (Institute of Advanced Engineering and Science, 2022)
In this paper, we investigate a hexagonal two-layer photonic crystal fiber based on surface plasmon resonance (HT-PCF-SPR) which is easy to fabricate as a sensor for detecting the refractive index of analytes. After performing numerical simulations using COMSOL multiphysics based on the finite element method (FEM), it was found that the HT-PCF-SPR could detect the analyte's refractive index in the range 1.34-1.37 RIU and in the wavelength range from 730 nm to 810 nm. The plasmonic material used in the design is gold with a thickness of 40 nm which is located outside the layer and in two opposite air holes in the core. The HT-PCF-SPR design has good performance in detecting analytes, it is found that the sensitivity in detecting analytes is 2,000 nm/RIU, meaning that every 1 RIU shift of analyte shifts the wavelength by 2000 nm. Meanwhile, the sensor resolution obtained from the design is 6.67×10-5 RIU, and it is found that the larger the air hole, the greater the confinement loss value.